A9.14 Regulatory T Cell Abnormalities in Patients with SLE Suggest an IL-2-Based Immunotherapy. (25th February 2013) - Spee, C von; Wassermann, N; Humrich, JY; Riemekasten, G
Abstract : Background: Phenotypic and quantitative abnormalities of regulatory T cells have been described in association with systemic lupus erythematosus (SLE). Further, an impaired production of IL-2, the essential cytokine for Treg homeostasis, has been described for T cells from SLE patients. Here, we aim to substantiate the link between IL-2 deficiency and Treg abnormalities in SLE and to provide the basis for an IL-2 based immunotherapy. Methods: Phenotype, frequency and homeostatic status of Foxp3+CD127lo Treg and conventional Foxp3- T cell (Tcon) subsets were analysed by multi-colour flow-cytometry of PBMCs from SLE patients and healthy donors ex vivo and after in vitro low-dose IL-2 treatment. Disease activity was determined according to the SLE activity index (SLEDAI). Two-tailed Mann-Whitney U test or 2-way ANOVA test were used for statistical analysis between patient or treatment groups, Spearman's rank coefficient was used to calculate correlations with disease activity. Results: The frequency of CD25+ cells among Treg was significantly reduced in SLE patients compared to HC. Analysis of Ki67 expression revealed that proliferation was significantly increased in Tcon from SLE patients, resulting in a reduced Treg to Tcon proliferation ratio in SLE patients. The proliferation ratio correlated positively with the frequency of CD25+ Treg and inversely with disease activity. Treatment of SLE PBMCs with low-dose IL-2 in vitro resulted in increased frequencies of CD25+ cells among Treg and increased CD25 expression levels on Treg. Treg, but not Tcon proliferation was significantly increased under low-dose IL-2 treatment compared to untreated controls. Discussion: Similar to what has been observed in lupus-prone mice and IL-2 -/- mice, Treg from SLE patients show the classical hallmarks of IL-2 deficiency with loss of CD25 expression and impaired homeostasis. Our in vitro results show that these Treg defects can be restored by low-dose IL-2 treatment, suggesting IL-2 as a novel therapeutic target for SLE.